Formulasi dan Uji Iritasi Sediaan Body Scrub dari Ekstrak Pegagan (Centella Asiatica) dengan Penambahan Scrubber Cangkang Telur Ayam - Niken Maya Suryani; Hasriyani Hasriyani; Bintari Tri Sukoharjanti (Universitas Pahlawan Tuanku Tambusai, 2026)
Centella asiatica is known to possess anti-inflammatory, antioxidant, and skin regeneration activities. The use of natural ingredients in cosmetic formulations has gained increasing attention, including the utilization of chicken eggshell waste, which is rich in calcium carbonate, as an environmentally friendly scrubber alternative to microplastics. This study aimed to formulate and evaluate a body scrub preparation containing Centella asiatica extract at concentrations of 1%, 2%, and 3% combined with chicken eggshell powder as a scrubber agent. The evaluation included physical quality tests consisting of organoleptic properties, pH, homogeneity, viscosity, and spreadability, as well as irritation and hedonic tests on panelist. Data analysis was performed using normality tests (Shapiro–Wilk) and homogeneity of variance tests (Levene or Bartlett), followed by One-Way ANOVA and post hoc analysis. The irritation test was conducted using the open patch method for 5 minutes to observe the presence or absence of irritation reactions. Hedonic testing was carried out using questionnaires assessing aroma, color, and texture preferences. The results showed that Centella asiatica extract contained flavonoids, tannins, and saponins. All formulations (F0, F1, F2, and F3) met the physical quality requirements for body scrub preparations, including organoleptic properties, homogeneity, viscosity, and spreadability. The irritation test demonstrated that all formulations were non-irritating and safe for skin application. The hedonic test indicated that the most preferred formulation by the panelists was F1 containing 1% Centella asiatica extract.